Perception and Adaptation Strategies of Pond Farmers toward Local Climate Changes in Muara Badak Sub-district of Kutai Kartanegara District - Rusmaniansyah Rusmaniansyah; Bambang Indratno Gunawan, Komsanah Sukarti (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The objectives of this study are: (1) to know pond farmers community perceptions over local climate change in Muara Badak Sub-district; (2) To identify adaptation strategies developed by pond farmers to cope with local climate change in Muara Badak Sub-district; (3) To analyze local climate change impact to farmers’ welfare in Muara Badak Sub-district and (4) To analyze the impact of pond area, temperature, rainfalls and rainy days variables to shrimp production in Muara Badak Sub-district. Study location was in Muara Badak Sub-district, Kutai Kartanegara District. Field data collection was done for 3 (three) months from June to September 2016. Purposive sampling method was applied to interview 40 pond farmer respondents and key informants consisting of Field Officer 2 people, Pond Farmer Group 2 people, District Office of Fisheries Affairs 1 people and Office of Samarinda District Navigation 2 people. Data analysis were the approach of perception analysis, descriptive statistics, Farmers’ Terms of Trade analysis and multiple regression model analysis. Results showed that farmers’ community in Muara Badak Sub-district perceived the local climate change has been impacting to shrimp pond production. Main adaptation strategy that is developed by farmers to face local climate change including changes of temperature, rainfalls and sea mean level in Muara Badak Sub-district is the water management in the sluite gates to frequently change water circulation and replacememnt. Local climate change does not impact to farmers’ welfare in the studied location based on the Terms of Trade value between 2015 (0.98) and 2016 (1.14). On the basis of multiple regression analysis, we knew that 80.7% of the shrimp production variation was affected by pond area, temperature, rainfalls and rainy days. Pond area variable very significantly affected to production while the remaining variables did not significantly affect it.